LEGAL STATUS OF PHARMACEUTICAL INDUSTRY SECRECY IN THE UAE LEGAL SYSTEM - Jehad Saleh Bani Younis (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Facing the problem of matching growth and status, starting work, starting work, starting work, starting work, starting work, starting work, starting work, and the United Arab Emirates. This harmonization - by approving a set of exceptions of this nature has some of the effects and the secret idea behind it.As we see him, he relied on the idea of ??public order in order to set some exceptions related to the inventions themselves by excluding some of them from the requirement to obtain a patent certificate, which is stipulated in Article 6 of the Law on the Organization and Protection of Industrial Property, and he also made exceptions related to the rights established for the inventor, which are It gives him the power to monopolize and dominate the invention if the inventor has what is in conflict with the objectives of scientific research, which is stipulated in Article 19 of the aforementioned law, and we see that the UAE legislator has organized the idea of ??compulsory licensing contracts for pharmaceutical products in accordance with the interests of both the licensee and the licensee.